Wakaf Abdan Dalam Pendidikan Islam - Ainur Rofiq, Ahmad; Makhrus Ali, Muhammad; Alfarisi, Salman (Cv. Kalimasada Group, 2023)
Management of productive waqf in Indonesia has received legal protection. Through Law no. 41 of 2004 concerning waqf, actually waqf management is directed at the productive sector. Pondok Modern Darussalam Gontor, East Java is one of the relatively successful nazhirs. Since the beginning of its development, Pondok Modern Darussalam Gontor has called itself a